An Approach to Integrate Collections of Images and Relational Databases - Jasinski, P. J.; Meinzer, H.-P.; Köhler, C. O.; Sandblad, B. (Methods of Information in Medicine, 1988)
The structure of computer-processed images is described. This is the basis for presenting a method to integrate traditional database concepts and images which represent a certain class of nonformatted, heterogeneous information. The method presented consists of a special, surrogate Image data type and a design of Image Directory, which associates formatted data, raw digital images stored conceptually in the form of a file of variable length, bit string records, and look-up tables. Beside individual and aggregate-oriented retrieval, some tools supporting more sophisticated analyses of images are also suggested. In order to make the description of solutions clear and truly methodological, a basic notion of the relational database technology and a de facto standard query language (SQL) have been applied. The method presented can be used to build various medical applications where images and/or graphics constitute an important fraction of information.Die Struktur computerverarbeiteter Bilder wird beschrieben. Das ist die Grundlage für die Darstellung einer Methode zur Integration traditioneller Datenbankkonzepte und Bilder, welche eine bestimmte Klasse nichtformatierter, heterogener Information bilden. Die dargestellte Methode besteht aus einem speziellen Bilddatentyp und einem Plan eines Bildverzeichnisses, welches formatierte Daten, rohe digitale Bilder, begrifflich gespeichert in Form einer Datei variabler Länge, Bitkettensätze und Farbtabellen verbindet. Neben individuell und auf das gesamte Datenmaterial ausgerichtetem Retrieval werden auch einige Werkzeuge zur Unterstützung komplizierterer Bildanalysen vorgeschlagen. Um die Beschreibung von Lösungen klar und wirklich methodisch zu gestalten, wurden eine grundlegende . Vorstellung der relationalen Datenbanktechnologie und eine de facto Standard-SQL-Sprache angewandt. Die dargestellte Methode kann zum Aufbau verschiedener medizinischer Anwendungen benutzt werden, bei denen Bilder und/oder Graphiken einen wichtigen Teil der Information bilden.
Keywords: Digital Images; Relational Database; SQL; Image Retrieval